1991
DOI: 10.1128/aac.35.10.2037
|View full text |Cite
|
Sign up to set email alerts
|

Use of ampicillin-sulbactam for treatment of experimental meningitis caused by a beta-lactamase-producing strain of Escherichia coli K-1

Abstract: We evaluated the pharmacokinetics and therapeutic efficacy of ampicillin combined with sulbactam in a rabbit model of meningitis due to a 1-lactamase-producing strain of Escherichia coli K-1. Ceftriaxone was used as a comparison drug. The MIC and MBC were 32 and >64 ,ug/ml (ampicillin), >256 and >256 ,ug/ml (sulbactam), 2.0 and 4.0 jig/ml (ampicillin-sulbactam [2:1 ratio, ampicillin concentration]) and 0.125 and 0.25 ,ug/ml (ceftriaxone). All antibiotics were given by intravenous bolus injection in a number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Similarly, concentrations of bacteria in CSF tended to increase throughout therapy in all animals given either drug alone. In contrast, the combination of piperacillin with tazobactam produced bactericidal activity in the CSF in vivo at all dosages that were investigated ( Piperacillin (80) 6 0.45 ± 0.29 2 (6) Piperacillin (200) 6 0.53 ± 0.10 3 (8) Tazobactam ( (20,23) and for sulbactam in the infected CSF of rabbits (10) and humans (9). In contrast, concentrations of clavulanic acid in human infected CSF are low, as a result of modest penetration and dosage limitations in patients (2,5).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, concentrations of bacteria in CSF tended to increase throughout therapy in all animals given either drug alone. In contrast, the combination of piperacillin with tazobactam produced bactericidal activity in the CSF in vivo at all dosages that were investigated ( Piperacillin (80) 6 0.45 ± 0.29 2 (6) Piperacillin (200) 6 0.53 ± 0.10 3 (8) Tazobactam ( (20,23) and for sulbactam in the infected CSF of rabbits (10) and humans (9). In contrast, concentrations of clavulanic acid in human infected CSF are low, as a result of modest penetration and dosage limitations in patients (2,5).…”
Section: Resultsmentioning
confidence: 99%
“…In the last few years, however, an increase in resistance, especially among Enterobacteriaceae, has been reported, resulting from a continuous spread of broad-spectrum β-lactamases. Guerra-Romero et al (1991) reported a combination of a penicillin-derivative drug (ampicillin) and sulbactam, for the treatment of experimental meningitis caused by a β-lactamase producing strain of E. coli K-1.…”
Section: Introductionmentioning
confidence: 99%
“…Again, in contrast to in-vitro experiences, which show that /J-lactams achieve maximal activity at concentrations only slightly above the MBC, infection model studies have found a strong dose-response curve between antibiotic concentration and bacteria] killing rates in the CSF. The maximum attainable bacterial killing rate is approximately 1 log, 0 cfu/mL/h at very high doses, and is independently of the class of antibiotic and infecting pathogen examined (Tauber et al, 1984a(Tauber et al, , 1985aKern et al, 1990;Guerra-Romero et al, 1991).…”
Section: In-vitro Versus In-vivo Activitymentioning
confidence: 96%
“…Many experimental studies have documented that antibiotics have to exceed the in-vitro MBC of the infecting pathogen by at least 10-30-fold (Tauber et al, 1984a(Tauber et al, , 1985aKern et al, 1990;Guerra-Romero et al, 1991). The reasons for this reduced activity of antibiotics in CSF compared with that in vitro are not completely clear, but the specific milieu of the CSF may be a contributing factor, since time-kill curves performed in CSF ex vivo with penicillin G against S. pneumoniae showed that three to ten times higher concentrations were needed to reach the same maximal bacterial activity as in broth (Tauber et al, 1984a).…”
Section: In-vitro Versus In-vivo Activitymentioning
confidence: 99%